The clinical and dermoscopic features of extremity melanomas - Cengiz, FATMA PELİN; CENGİZ, FATMA PELIN; Emiroglu, NAZAN; EMİROĞLU, NAZAN; HOFMANN-WELLENHOF, Rainer (My University, 2015)
Background and Design: Dermoscopy is a noninvasive tool that helps differentiate structures that cannot be seen by naked eye. Dermoscopic and clinical features of malignant melanomas of the extremities are not well described in the literature. Therefore, in this study, we aimed to determine the dermoscopic and clinical characteristics of melanoma of the extremities.